Characterization of an Anti-Ebola Virus Hyperimmune Globulin Derived From Convalescent Plasma. (27th August 2021) - Ciencewicki, Jonathan M; Herbert, Andrew S; Storm, Nadia; Josleyn, Nicole M; Huie, Kathleen E; McKay, Lindsay G A; Griffiths, Anthony; Dye, John M; Willis, Todd; Arora, Vikram
Abstract : This article describes characterization of a purified anti-Ebola virus intravenous immunoglobulin manufactured from pooled convalescent plasma. In vitro efficacy was demonstrated by neutralization capacity in pseudovirion and live virus assays; in vivo efficacy was demonstrated in a mouse model. Abstract: Background: Convalescent plasma has been used to treat many viral diseases including Ebola. The manufacture of a purified anti-Ebola virus (EBOV) intravenous immunoglobulin (IVIG) from pooled convalescent plasma is described in this paper. Methods: An enzyme-linked immunosorbent assay (ELISA) targeting an EBOV surface glycoprotein antigen was used to determine the immunoglobulin titer of pooled plasma and purified anti-EBOV IVIG. Anti-EBOV IVIG was also tested in neutralization assays using a vesicular stomatitis virus pseudovirion expressing EBOV glycoprotein on its surface and with live EBOV. Finally, the efficacy of the anti-EBOV IVIG was assessed in a mouse model of EBOV infection. Results: In the ELISA, the anti-EBOV IVIG was shown to have a 7-fold increase in immunoglobulin G (IgG) titer over pooled convalescent plasma. In both the pseudovirion and live virus assays, the anti-EBOV IVIG showed approximately 5- to 6-fold increased potency over pooled plasma. Anti-EBOV IVIG also significantly improved survivability in mice infected with the virus when administered concurrently or 2 days after infection. Conclusions: These data support this purified anti-EBOV IVIG merits additional investigation and clinical trials for treatment and postexposure prophylaxis of Ebola virus disease. The experience gained can be applied to manufacture hyperimmune globulins against other emerging viruses.